Bizarre parosteal osteochondromatous proliferative lesion of the hallux - Siyo, Zuko; Saragas, Nikiforos Pandelis; Ferrao, Paulo Norberto Faria (Journal of the Foot & Ankle, 2024)
Foot tumors are a rare occurrence, which can make diagnosis and management difficult. Certain benign tumors can be locally aggressive, with a rapid progression resembling a malignancy. We present a case of bizarre parosteal chondromatous proliferative (BPOP) lesion, also known as Nora lesion, arising from the sesamoid. This is a benign lesion with overlapping clinical and radiological features of a malignant neoplasm. Highlighting classic BPOP characteristics is crucial in avoiding potentially incorrect management and resulting morbidity. Levels of evidence IV; Therapeutic studies; Case Report